ANALYSIS OF FACTORS INFLUENCE SMOKING BEHAVIOR IN POOR HOUSEHOLDS IN WEST SUMATERA PROVINCE - Hefrizal Handra; Zamzami Zamzami (AFEBI Economic and Finance Review, 2016)
This research is purposed to learn the behaviors of poor households in managing their income for buying cigarettes using data from the National Social Economic Survey of West Sumatera Province in 2013 using OLS method as a tool of analysis.Results of the analysis show that the cigarette spending in percentage of income in smoker households in West Sumatera Province is very large, far larger than the percentage of spending for education and health. Household cigarette spending is influenced by income factors, cigarette prices, number of adult male household members, area of residence, age category of the household head, and education of the household head.JEL Classification: D10, D31, P46Keywords: Cigarette Spending, OLS Regression, Smoking Household, Taste Intervention